Peran Pemerintah dalam Mendorong Kualitas Pelayanan Pendidikan di Indonesia - Ilham, Dodi; S, Muh. Rizal; Karunia, Luki; Saleh, Sirajuddin; Brata, Joko Tri (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2023)
This research discusses the crucial role of the government in advancing the quality of education services as the background for the need for quality education for the progress of a nation. The purpose of this research is to investigate the role of the government in the context of education, including financing, regulation, curriculum, teacher training, and supervision in Indonesia. In this research method, we analyze education policies implemented by the government and gather data from various sources, including surveys, interviews, and related literature. The results of this research highlight the importance of adequate budget allocation, effective regulation, relevant curriculum, sustainable teacher training, and strict supervision as key factors in improving the quality of education services. This research provides valuable insights into how the government can play a role in optimizing the education system for a brighter future.